Emerging role of exosomes in arterial and renal calcification. (September 2021) - Bano, Shumaila; Tandon, Simran; Tandon, Chanderdeep
Exosomes are small, cell-derived vesicles of 30–100 nm that participate in cell-to-cell communication. They are released by many cells, such as dendritic cells (DC), lymphocytes, platelets, epithelial cells, endothelial cells (EC), and are found in most body fluids, including blood, saliva, urine, and breast milk. The exosomes released from cells within the cardiovascular system may contain either inhibitors of calcification in normal physiological conditions or promoters in the pathological environment [atherosclerosis (AS), and Chronic Kidney Disease (CKD)]. The exosomes of the vascular smooth muscle cells (VSMCs) are novel players in vascular repair processes and calcification. Several studies have shown that the cytoplasmic contents of exosomes are rich in a variety of proteins, nucleic acids, and lipids. Currently, exosomal micro RNAs and proteins are increasingly being recognized as biomarkers for the diagnosis of several diseases, including those of kidney and liver, as well as different types of cancer. In this review, we summarize recent advances in the role of exosomes in vascular calcification and their potential applications as diagnostic markers as well as a brief overview of the role of stem cell-derived exosomes in cardiovascular diseases.